How to sell refurbished smartphones? An investigation of different customer groups and appropriate incentives. (20th March 2017) - Mugge, Ruth; Jockin, Boris; Bocken, Nancy
Abstract: As smartphones are being replaced at an increasing rate, it becomes more and more important to find ways to reuse (parts of) existing phones. This research investigates the potential of selling refurbished smartphones using a quantitative study. An online survey was conducted questioning 250 respondents, in which the perceived consumer risks and benefits associated with refurbished phones were investigated. Furthermore, we studied the impact of various incentives that companies can employ to improve consumers' purchase intention of refurbished phones. Through a cluster analysis six distinct customer groups were identified. Our sample demonstrated a positive attitude towards refurbished smartphones, with most potential for three out of our six customer groups (46% of our sample). This indicates that refurbished smartphones can be a market success. It was found that perceived environmental benefits and awareness of refurbishing have a positive impact on the consumers' purchase intention for refurbished smartphones. Most of the highest scoring incentives for purchasing refurbished smartphones were product-related and included improved battery life, guaranteed software updates and upgraded performance, indicating a need for continued performance. This research contributes to our theoretical understanding of consumer responses to refurbished smartphones and can help companies in launching these products successfully. Highlights: This paper explores incentives affecting consumer responses to refurbished phones. Different customer groups vary in their response to refurbished phones. Creating awareness enhances consumers' purchase intention of refurbished phones. Making environmental benefits more apparent enhances consumers' purchase intention. Incentives that ensure continued performance influence purchase intention the most.